Evaluation of minimum service standards for maternal health services at a primary health center - Rts Nurul Hafizhoh Agusriani; Arnild Augina Mekarisce; Muhammad Syukri; Adila Solida (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Minimum Service Standards are mandatory benchmarks for local governments and primary healthcare facilities to ensure the provision of essential maternal health services. Their achievement is important for improving antenatal care and reducing maternal morbidity and mortality. Purpose: To evaluate the achievement of Minimum Service Standards for maternal health services. Method: This qualitative evaluative study used a descriptive approach and the logic model framework, covering input, process, and output components. The study was conducted from November 2025 to August 2026. Fourteen informants were selected purposively, including the head of the primary health center, the maternal and child health coordinating midwife, a physician responsible for the maternal and child health cluster, six implementing midwives, and five pregnant women. Data were collected through in-depth interviews, observation, and document review and were analyzed thematically. Data credibility was supported through source and method triangulation. Results: Human resources were generally adequate in number and educational qualifications, although access to technical training was uneven. Maternal health facilities and basic equipment were available, but ultrasound services were underutilized because of the reassignment of trained physicians and limited service-room capacity. Antenatal care procedures and dual recording through manual registers and the e-Cohort system were generally implemented according to standard operating procedures. However, funding constraints affected outreach activities. Coverage of the first antenatal visit was 81.8%, while coverage of the sixth antenatal visit was 71.9%, both below the national target of 100%. Delayed first visits, refusal of triple elimination screening, sociocultural beliefs, and incomplete continuity of care contributed to the low achievement. Conclusion: Maternal health Minimum Service Standards at Penyengat Olak Primary Health Center have not yet reached the national target despite generally adequate human resources and service procedures. Improving technical capacity, continuity of antenatal care, community education, outreach financing, and cross-sectoral collaboration is necessary to improve maternal health service coverage.